2003
DOI: 10.1167/iovs.03-0258
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Mobilization and Cell Contraction after Muscarinic Cholinergic Stimulation of the Chick Embryo Lens

Abstract: The localization of ChAT in the differentiating fibers of the lens indicates that acetylcholine is synthesized during differentiation and modulates morphogenesis and elongation of mAChR-positive progenitor cells in the equatorial zone. The carbachol-induced contraction indicates that the embryonic muscarinic system may be involved in the regulation of cellular movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…The responding cells in our studies may correspond to the population of chicken annular pad cells responding to muscarinic acetycholine receptor stimulation with a [Ca 2ϩ ] i rise (Oppitz et al, 2003). We suggest that GABA and Ach may operate in concert as described previously for the chick retinal ventricular zone (Pearson et al, 2002) where the two neurotransmitters act synergistically to induce [Ca 2ϩ ] i rise.…”
Section: ؉ ] I In Equatorial Cells Of Intact Newborn Lensessupporting
confidence: 78%
“…The responding cells in our studies may correspond to the population of chicken annular pad cells responding to muscarinic acetycholine receptor stimulation with a [Ca 2ϩ ] i rise (Oppitz et al, 2003). We suggest that GABA and Ach may operate in concert as described previously for the chick retinal ventricular zone (Pearson et al, 2002) where the two neurotransmitters act synergistically to induce [Ca 2ϩ ] i rise.…”
Section: ؉ ] I In Equatorial Cells Of Intact Newborn Lensessupporting
confidence: 78%
“…Striking functional and structural similarities between lens fiber cells and neurons are observed in the regulation of vesicle trafficking and the involvement of Alzheimer proteins in this process in the normal state and during disease (Frederikse and Zigler, 1998;Li et al, 2003;Frederikse et al, 2004). The spatiotemporal expression of GAD in the differentiating primary fiber cells of the mouse lens shows a remarkable similarity to the expression of choline acetyltransferase (Chat, the acetylcholine [ACh] -synthesizing enzyme) in chicken differentiating lens fibers (Oppitz et al, 2003). Especially noteworthy is the high accumulation of GAD and Chat at the apical and basal tips of the elongating fibers, suggesting that GABA may be involved in the reorganization of the cytoskeleton during fiber elongation, as suggested for ACh (Oppitz et al, 2003).…”
Section: Lens As a Model To Study The Nonsynaptic Gaba Signaling Durimentioning
confidence: 84%
“…The spatiotemporal expression of GAD in the differentiating primary fiber cells of the mouse lens shows a remarkable similarity to the expression of choline acetyltransferase (Chat, the acetylcholine [ACh] -synthesizing enzyme) in chicken differentiating lens fibers (Oppitz et al, 2003). Especially noteworthy is the high accumulation of GAD and Chat at the apical and basal tips of the elongating fibers, suggesting that GABA may be involved in the reorganization of the cytoskeleton during fiber elongation, as suggested for ACh (Oppitz et al, 2003). Finally, the lens affords a unique model to study the regulation of expression and intracellular role of multiple GAD isoforms, which, similar to the developing nervous system (Szabo et al, 1994;Katarova et al, 2000;Varju et al, 2001) are sequentially induced, but are spatiotemporally segregated.…”
Section: Lens As a Model To Study The Nonsynaptic Gaba Signaling Durimentioning
confidence: 99%
“…Experiments with isolated lens vesicles of the chick embryo showed that the peak reaction of muscarinic-induced calcium mobilization was followed by a contraction of the whole lens [Oppitz et al, 2003]. Addition of atropine in the plateau phase released the contraction so that the lens vesicle returned to its original diameter.…”
Section: Discussionmentioning
confidence: 99%